Observations of quiet-time moderate midlatitude L-band scintillation in association with plasma bubbles - Sreeja, V.; Haralambous, H.; Aquino, M. (Springer Verlag, 2017)
Observations of moderate night time amplitude scintillation on the GPS L1C/A signal were recorded at the midlatitude station of Nicosia, corresponding geographic latitude and longitude of 35.18˚N and 33.38˚E respectively, on a geomagnetically quiet day. The variations of slant total electron content (STEC) and amplitude scintillation index (S4) on the night of June 12, 2014, indicate the presence of electron density depletions accompanying scintillation occurrence. The estimated apparent horizontal drift velocity and propagation direction of the plasma depletions are consistent with those observed for the equatorial plasma bubbles, thus suggesting that the moderate amplitude L-band scintillation observed over Nicosia may be associated with the extension of such plasma bubbles. The L-band scintillation occurrence was concurrent with the observations of range spread F on the ionograms recorded by the digisonde at Nicosia. The height–time–intensity plot generated using the ionogram data also showed features which can be attributed to off-angle reflections from electron density depletions, thus corroborating the STEC observations. This observation suggests that the midlatitude ionosphere is more active even during geomagnetically quiet days than previously thought and that further studies are necessary. This is particularly relevant for the GNSS user community and related applications.